Kepemilikan Tanah Bagi Warga Negara Asing Di Indonesia - Agung Torang Sitohang; Desy Yolanda Br Bangun; Lidia Rumapea; Roselli Anjelina Lumbansiantar; Tasya Br Marbun; Widya Helen Anjalina Purba; Ramsul Nababan (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2024)
In current conditions, foreign nationals in Indonesia are not becoming fewer and fewer, but are actually increasing in number. There are several reasons why there are so many foreigners in Indonesia, one of which is the global flow and modernization factor, and another reason is to Increase multilateral cooperative relations with other countries, so it is felt necessary to provide easy access for foreigners to visit or live in Indonesia. However, foreigners are not allowed to control land with ownership rights, where if foreigners obtain ownership rights then the land is controlled by the state. The research method used in this research is a qualitative descriptive method with a normative juridical approach which analyzes legal norms from the perspective of literature study. Data was obtained through literature study, interviews and documentation. The research was carried out to find out how land rights are controlled by foreign citizens according to the UUPA and how the use rights and the end of legal relations for residential homes for foreign citizens are carried out. Land ownership for foreign citizens in Indonesia is generally limited and regulated by Law Number 5 of 1960. They can obtain use rights to land, but ownership rights are limited to certain forms of foreign investment. This is intended to protect national interests and prevent foreign investment or accumulation of land by foreign parties.